(untitled) (Al-Aasar, 2025)
Child labor is not a hallmark of a healthy society; rather, it reflects a failure to uphold children’s rights and imposes undue responsibilities on them. In Pakistan, the Constitution of 1973 addresses child labor through several provisions. Article 11 of the Constitution prohibits slavery, forced labor, and child labor; however, this prohibition is not absolute, as it only restricts child labor in hazardous environments such as factories and mines. Furthermore, Article 3 of the Constitution commits the state to eliminate all forms of exploitation and ensures that no individual is overburdened beyond their capacity. The state also guarantees free and compulsory education for children aged 5 to 16 years as a fundamental right and promises to enact protective legislation for women and children. Additionally, the family unit is given constitutional protection, requiring the head of the household to provide for the basic needs of the family. This research analyzes the constitutional framework of Pakistan (1973) and federal-level child labor laws, including both specific and general labor legislation. It highlights ambiguities, gaps, and inconsistencies in these laws and offers practical recommendations for legal reform to strengthen child protection mechanisms in the country.